Surface free energy, microstructure and performance of polyvinylidene fluoride (PVDF) membrane: the influence of hydrophilic porogens. Issue 1 (27th July 2022) - Yuan, Ao; Yang, Jing; Mu, Ruihua; Li, Hongji; Guo, Yingming; Zhao, Yamei; Hou, Haiyun
Abstract: Polyvinylidene fluoride (PVDF) membrane are widely used in water treatment due to its good physical and chemical properties, and the pores of PVDF membranes determine most of the characteristics of PVDF membrane. The hydrophilic porogens play an important role in the preparation of PVDF membranes and the regulation of membrane pores. In this work, three hydrophilic porogens with different quality components were used to prepare PVDF ultrafiltration membranes by the nonsolvent induced phase separation (NIPS) method. Through the Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM), mechanical strength, contact angle and other characterizations, the influence of hydrophilic porogens on the surface free energy, microstructure and performance of PVDF membrane were studied. The results suggest that lithium chloride (LiCl) can inhibit the formation of macropores and improve the mechanical strength of the membrane. Polyvinylpyrrolidone (PVP) can form through-hole through the PVDF membrane. All three hydrophilic porogens can increased the surface free energy of the PVDF membranes, where polyethylene glycol (PEG) had the most impact on the surface free energy.